The Critical Studies of Fucoxanthin Research Trends from 1928 to June 2021: A Bibliometric Review - Yam Sim Khaw (MDPI AG, 2021)
Fucoxanthin is a major carotenoid in brown macroalgae and diatoms that possesses a broad spectrum of health benefits. This review evaluated the research trends of the fucoxanthin field from 1928 to June 2021 using the bibliometric method. The present findings unraveled that the fucoxanthin field has grown quickly in recent years with a total of 2080 publications. Japan was the most active country in producing fucoxanthin publications. Three Japan institutes were listed in the top ten productive institutions, with Hokkaido University being the most prominent institutional contributor in publishing fucoxanthin articles. The most relevant subject area on fucoxanthin was the agricultural and biological sciences category, while most fucoxanthin articles were published in Marine Drugs. A total of four research concepts emerged based on the bibliometric keywords analysis: “bioactivities”, “photosynthesis”, “optimization of process’’, and “environment”. The “bioactivities” of fucoxanthin was identified as the priority in future research. The current analysis highlighted the importance of collaboration and suggested that global collaboration could be the key to valorizing and efficiently boosting the consumer acceptability of fucoxanthin. The present bibliometric analysis offers valuable insights into the research trends of fucoxanthin to construct a better future development of this treasurable carotenoid.